Tuning Electron-Transfer Driving Force in Photosynthetic Special Pair Models - Ramírez-Wierzbicki, Ivana; Sanchez Merlinsky, Luciano; Pieslinger, German E.; Domínguez, Sofía; Slep, Leonardo D.; Baraldo, Luis M.; Cadranel, Alejandro (Chemistry - A European Journal, 2024)
Visible-light excitation of a family of bimetallic ruthenium polypyridines with the formula [RuII(tpy)(bpy)(-CN)RuII(py)4L]n+ (RuRuLn+), where L=Cl−, NCS−, DMAP and ACN, was used to prepare photoinduced mixed-valence (PI-MV) MLCT states as models of the photosynthetic reaction center. Ultrafast transient absorption spectroscopy allowed to monitor photoinduced IVCT bands between 6000 and 11000 cm−1. Mulliken spin densities resulting from DFT and (TD)DFT computations revealed the modulation of the charge density distribution depending on the ligand substitution pattern. Results are consistent with PI-MV systems ranging from non-degenerate Class II to degenerate Class III or II/III, with electronic couplings between 1000 and 3500 cm−1. These findings guide the control electron localization-delocalization in charge-transfer/charge-separated excited states, like those involved in the photosynthetic reaction center.
CRIS-Team Scopus Importer:2024-11-29
Keywords: electron transfer; photosynthesis; redox asymmetry; solar energy conversion; transient absorption